2019
DOI: 10.1080/14786419.2019.1700505
|View full text |Cite
|
Sign up to set email alerts
|

A new xanthone and a biphenyl from the flower and twig extracts of Garcinia mckeaniana

Abstract: The phytochemical investigation of the flower and twig extracts of Garcinia mckeaniana yielded a new xanthone, mckeanianone F (1) and a new biphenyl, mckeaniabiphenyl (2) together with 15 known compounds. The isolated compounds were characterized using spectroscopic techniques and mass spectrometry. Some of the isolated compounds from the twigs exhibited antimalarial and cytotoxic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…G. mckeaniana Craib, locally named Xen mu, is found in secondary forests, especially in Sapa mountain and Thuan Chau‐Son La [4] . To date, phytochemical and biological studies on G. mckeaniana are quite limited [5–9] . This current study is the first to report the phytochemical isolation and structural elucidation of the new xanthone 1 and eight known analogs 2 – 9 from the AcOEt extract of G. mckeaniana leaves, together with their cytotoxic and α‐glucosidase inhibitory activities.…”
Section: Introductionmentioning
confidence: 83%
“…G. mckeaniana Craib, locally named Xen mu, is found in secondary forests, especially in Sapa mountain and Thuan Chau‐Son La [4] . To date, phytochemical and biological studies on G. mckeaniana are quite limited [5–9] . This current study is the first to report the phytochemical isolation and structural elucidation of the new xanthone 1 and eight known analogs 2 – 9 from the AcOEt extract of G. mckeaniana leaves, together with their cytotoxic and α‐glucosidase inhibitory activities.…”
Section: Introductionmentioning
confidence: 83%
“…The n -hexane extract of the Garcinia bancana leaves showed antioxidant activity according to 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) tests ( Putri et al, 2018 ). In the research of Auranwiwat and co-workers, cytotoxicity against KB cells of 1 was tested, but 1 was inactive to both cells with IC 50 > 50 µM ( Table 1 ) ( Auranwiwat et al, 2021 ).…”
Section: Diverse Biphenyls From Clusiaceae and Their Bioactivitymentioning
confidence: 99%
“…For the aim of searching for undiscovered natural products of Garcinia mckeaniana Craib, the constituents belonging to the flower and twig extracts of this plant were investigated by Auranwiwat and others and a biphenyl ( 19 ) was found ( Figure 3 ) in 2021 ( Auranwiwat et al, 2021 ). Garcinia mckeaniana , also called Xen mu, is a common plant that is widespread in the tropical secondary forests of Sapa town and Son La province of Vietnam in particular.…”
Section: Diverse Biphenyls From Clusiaceae and Their Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Xanthone derivatives have been reported to have antimalarial activity [18][19][20]. Furthermore, hydroxyxanthone as a derivative of xanthone also exhibited effective antimalarial activity [21]. It was also reported that thioxanthone derivatives exhibit good antimalarial activity [22][23].…”
Section: ■ Introductionmentioning
confidence: 99%